Klotho : Expression and Regulation at the Maternal-Conceptus Interface in Pigs - Yohan Choi; Heewon Seo; Jangsoo Shim; Sang-Hwan Hyun; Eunsong Lee; Hakhyun Ka (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Klotho (KL) is a single transmembrane protein composed of KL1 and KL2 repeats possessing β-glucuronidase activity and maintains calcium homeostasis in physiological state. It has been implicated in pigs that calcium is important for the establishment and maintenance of pregnancy, and our previous study has shown that transient receptor potential vanilloid type 6 (TRPV6), a calcium ion transporter, is predominantly expressed in the uterine endometrium during pregnancy in pigs. However, expression and function of KL in the uterine endometrium has not been determined in pigs. Thus, the present study determined expression and regulation of KL in the uterine endometrium during the estrous cycle and pregnancy in pigs. Real-time RT-PCR analysis showed that levels of KL mRNA decreased between Days 12 to 15 of the estrous cycle, and its expression showed a biphasic manner during pregnancy. KL mRNA was expressed in conceptuses and in chorioallantoic tissues during pregnancy. Explant culture study showed that expression levels of KL were not affected by treatment of steroid hormones or interleukin-1beta during the implantation period. Furthermore, levels of KL mRNA in the uterine endometrium from gilts carrying somatic cell nuclear transfer (SCNT)- derived embryos were significantly lower than those from gilts carrying natural mating-derived embryos on Day 12 of pregnancy. These results exhibited that KL was expressed at the maternal-conceptus interface in a pregnancy status- and stage-specific manner, and its expression was affected by SCNT procedure, suggesting that KL may play an important role in the establishment and maintenance of pregnancy in pigs